2015
DOI: 10.1080/15287394.2015.1021433
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Selected Phthalates by Gas Chromatography–Mass Spectrometry in Personal Perfumes

Abstract: A simple and fast method is proposed to analyze commercial personal perfumes. Our method includes measurement of phthalates, known to be major sources of endocrine disruptor chemicals (EDC), which originate from the less volatile fraction of perfumes. The quantification of phthalates were carried out directly with no sample preparation required on 30 samples of commercial products using gas chromatography and mass spectrometry (GC-MS) as a detector. The total concentrations of 15 investigated compounds ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“… 10 13 For some phthalate diesters, the use of consumer products and indoor exposures are major contributors to human exposure. 14 17 Similarly, for some flame retardants, dust is a significant contributor to exposure, 18 20 while the contribution of the indoor environment to total exposure of PFASs is less well characterized. 21 , 22 The chemical properties, sources, exposure pathways and major health effects associated with each chemical class are reviewed in the following sources: phthalates, 16 , 23 26 flame retardants, 25 , 27 , 28 environmental phenols, 25 , 26 , 29 , 30 synthetic fragrances, 29 , 31 , 32 and PFASs.…”
Section: Introductionmentioning
confidence: 99%
“… 10 13 For some phthalate diesters, the use of consumer products and indoor exposures are major contributors to human exposure. 14 17 Similarly, for some flame retardants, dust is a significant contributor to exposure, 18 20 while the contribution of the indoor environment to total exposure of PFASs is less well characterized. 21 , 22 The chemical properties, sources, exposure pathways and major health effects associated with each chemical class are reviewed in the following sources: phthalates, 16 , 23 26 flame retardants, 25 , 27 , 28 environmental phenols, 25 , 26 , 29 , 30 synthetic fragrances, 29 , 31 , 32 and PFASs.…”
Section: Introductionmentioning
confidence: 99%
“…Their basic chemical structure is phthalic acid with two side chains (they may be branched or linear), which can be alkyl, benzyl, phenyl, cycloalkyl, or alkoxy groups (Abdel-Daiem et al, 2012). Di(2-ethylhexyl) phthalate (DEHP) is a diester of phthalic acid used as a plasticizer for polyvinyl chloride (PVC), which increases the flexibility of the plastic, enabling a wide range of products to be manufactured (Benjamin et al, 2015;Orecchio et al, 2015). DEHP is used in consumer goods, food contact materials, flooring and wall covering, and medical devices (i.e., blood storage bags, hemodialysis tubing, oxygenation Science of the Total Environment xxx (2016) xxx-xxx ⁎ Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection (LOD) is defined as the quantity yielding a detector response approximately equal to thrice the background noise and calculated by the standard deviation of the response (σ) and the slope of the calibration curves [ 5 , 14 , 15 ]. The limit of quantitation (LOQ) is the lowest amount that can be analyzed within acceptable precision and accuracy at a signal to noise ratio of 10 [ 19 ]. In this study, LOD and LOQ were measured, and the obtained data are shown in Table 5 .…”
Section: Resultsmentioning
confidence: 99%